Real-Time systems development - Williams, Rob (Colección de libros electrónicos de ULoyola, 2006)
Real-Time Systems Development introduces computing students and professional programmers to the development of software for real-time applications. Based on the academic and commercial experience of the author, the book is an ideal companion to final year undergraduate options or MSc modules in the area of real-time systems design and implementation